Mustawa Fahm Al-mufradat Al-lughawiyyah Laday Talabat Al-markaz Al-tamhidi Bi Jamiʽah Al-ʽulum Al-islamiyyah Al-maliziyyah - Mohamad Hazwan A. Rahman (NUN Gemilang Enterprise, 2024)
Vol. 1 No. 2 (2021): (April - June)